Real-time supply chain - a blockchain architecture for project deliveries - Helo, Petri; Shamsuzzoha, A.H.M. (Elsevier, 2020)
Real-time tracking and tracing are important in providing a unified view of global supply chains consisting of several parties. This paper illustrates the needs and requirements for managing supply chains in multi-company project environments by adopting various tracking and tracing technologies. This kind of tracking and tracing is especially needed within distributed architectures engaged in project-based businesses, where several vendors are involved in a single project. Such tracking and tracing data can be used extensively to generate key performance indicators, which can be used to measure and control supply chain processes. This paper also proposes a pilot system of a cloud-based portal for real-time tracking and tracing of logistics and supply chains. This portal is formed by the combination of RFID, IoT and blockchain technology into an integrated real-time view. RFID (Radio Frequency Identification) and IoT (Internet of Things) provides real-time information or data, while blockchain technology is used to provide a chain of immutable transactions. The architecture of the proposed portal system is connected to transport companies, tracking devices, consolidation points and suppliers. The pilot study also illustrates the benefits and advantages of such a portal system.
Keywords: supply chain management; real-time; blockchain; key performance indicators; fi=Tuotantotalous|en=Industrial Management|